2012
DOI: 10.4314/ajtcam.v9i4.18
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of a Novel Four-Electrode Device System for Monitoring Skin Impedance

Abstract: Qi, meridians, and acupoints are important issues in Chinese medicine. One of the theories claims that acupuncture points and meridians have unique electrical properties. The associations between acupuncture points or meridians and special electrical properties are still under debate. In the current study, we introduced and explained a device for this kind of research and evaluated the reliability of this device as well as effects of pressure, cleaning the skin by alcohol and exfoliation on electrical skin mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…By applying age limits and using control points on the other side of each person's body, the effects of some confounding factors such as age and race on impedance were minimised. 28 We used a fourelectrode device which was designed and tested for this study. This device had just 12 probes, so only six points on each side of the body could be chosen; this was a limitation of our research.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…By applying age limits and using control points on the other side of each person's body, the effects of some confounding factors such as age and race on impedance were minimised. 28 We used a fourelectrode device which was designed and tested for this study. This device had just 12 probes, so only six points on each side of the body could be chosen; this was a limitation of our research.…”
Section: Discussionmentioning
confidence: 99%
“…31 However, some studies have shown that the whole or part of skin impedance varies in different races, depending on factors such as age, environment and race. 32 33 In another study, we examined some confounding factors such as environment, moisture and pressure of the probe on the skin, and concluded that these factors had no impact on the results; 28 we omitted known confounding factors such as age by setting an age limit. However, in this study, we used a 5 mm diameter probe.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other inventors have also claimed to identify health problems using similar devices [21], but this function has been questioned by the scientific community [22]. Shima et al developed a four-electrode device system that enables stable measurement of electrical skin impedance in acupuncture [23]. Yang et al designed an acupoint recognition device by improving the acupoint electric resistance detection technique of the two-electrode method in combination with mechanical structure design and embedded control techniques [24].…”
Section: A Related Workmentioning
confidence: 99%